2012
DOI: 10.1042/bj20111747
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary characterization of the cytosolic glutathione transferase proteome from Drosophila melanogaster

Abstract: The cytosolic GST (glutathione transferase) superfamily has been annotated in the Drosophila melanogaster genome database. Of 36 genes, four undergo alternative splicing to yield a total of 41 GST proteins. In the present study, we have obtained the 41 transcripts encoding proteins by RT (reverse transcription)-PCR using RNA template from Drosophila S2 cells, an embryonic cell line. This observation suggests that all of the annotated DmGSTs (D. melanogaster GSTs) in the proteome are expressed in the late embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 50 publications
3
78
1
9
Order By: Relevance
“…Furthermore, 63% of our 195 ageing signature genes for which expression level correlated with decreased survival with age were identified as ageing genes in the same study14 (hypergeometric test for enrichment, p < 1 × 10e-22). An analysis of the correlated genes for the control cohort using the Flymine database15 revealed that the pathways in which these genes are involved are significantly enriched in a number of pathways and GO annotations related to xenobiotic metabolism, glutathione metabolism and immune response pathways1617. This is consistent with current theories of ageing192018.…”
Section: Resultssupporting
confidence: 68%
“…Furthermore, 63% of our 195 ageing signature genes for which expression level correlated with decreased survival with age were identified as ageing genes in the same study14 (hypergeometric test for enrichment, p < 1 × 10e-22). An analysis of the correlated genes for the control cohort using the Flymine database15 revealed that the pathways in which these genes are involved are significantly enriched in a number of pathways and GO annotations related to xenobiotic metabolism, glutathione metabolism and immune response pathways1617. This is consistent with current theories of ageing192018.…”
Section: Resultssupporting
confidence: 68%
“…There are at least 41 DmGSTs found in Drosophila melanogaster [20], 37 AgGSTs in A. gambiae [21], 12 AmGSTs in A. mellifera [22] and 23 BmGSTs in B. mori [23]. In our previous study, 10 GSTs were identified from L. migratoria .…”
Section: Discussionmentioning
confidence: 92%
“…The CG6673 gene produces two alternatively spliced products, isoforms A and B ( Figure 1 ). Recently, these four GSTO genes were named sepia, GstO1, GstO2 , and GstO3 , respectively [ 2 ]. The average sequence identities/similarities are high, at 43% -65%/66% -82%, based on the amino acid sequence alignment of the different isoforms of GSTO [ 11 ].…”
Section: Gsto Genes In Drosophilamentioning
confidence: 99%
“…These enzymes provide protection against carcinogens, therapeutic drugs, and several types of cellular oxidative damage [ 1 ]. Based on their amino acid sequences and substrate specificities, GSTs are grouped into at least ten classes: α , δ , ε , κ , μ , π , σ , θ , ζ , and ω [ 2 ].…”
Section: Introductionmentioning
confidence: 99%